## Derivatives

Calculate the second derivative of (x^8)-(x^2)+2

##
__
__**Hint**

**Hint**

The power rule for the first derivative:

$$$\frac{d}{dx}[x^n]=n\cdot x^{n-1}$$$

##
__
__**Hint 2**

**Hint 2**

Using the power rule for the first derivative, and applying it twice, we’ll get the second derivative power rule:

$$$\frac{d^2}{dx^2}[x^n]=\frac{d}{dx}\frac{d}{dx}[x^n]=\frac{d}{dx}[nx^{n-1}]=n\frac{d}{dx}[x^{n-1}]=n(n-1)(x^{n-2})$$$

Using the power rule for the first derivative, and applying it twice, we'll get the second derivative power rule:

This calculus problem can be written as:

$$$\frac{d^2}{dx^2}(x^8-x^2+2)=\frac{d^2}{dx^2}(x^8)-\frac{d^2}{dx^2}(x^2)+\frac{d^2}{dx^2}(2)$$$

Applying the 2nd power rule to the first section of the derivative with
$$n=8$$
:

$$$\frac{d^2}{dx^2}[x^n]=n(n-1)(x^{n-2})\rightarrow\frac{d^2}{dx^2}(x^8)=56x^6$$$

Applying the 2nd power rule to the second section of the derivative with
$$n=2$$
:

$$$\frac{d^2}{dx^2}[x^n]=n(n-1)(x^{n-2})\rightarrow\frac{d^2}{dx^2}(x^2)=2$$$

Applying the constant rule to the third section of the derivative:

$$$\frac{d^2}{dx^2}[2x^0]=0$$$

Finally,

$$$\frac{d^{2}}{dx^{2}}(x^{8})-\frac{d^{2}}{dx^{2}}(x^{2})+\frac{d^{2}}{dx^{2}}(2)=56x^6-2$$$

$$$56x^6-2$$$